Preferences Test of Brown Lady Bug Riptortus linearis Fabr. (Hemiptera : Alydidae) on Soybeans (Glycine max L.), Greenbeans (Vigna radiata L.) and Orok-orok (Crotolaria pallida Aiton.) in Screenhouse - ricky arbiansyah; Marheni Sembiring; Fatimah Zahara (Universitas Sumatera Utara, 2016)
The objective of the research was to know the preferences food of brown lady bug (R. linearis) on the pod of soybeans, greenbeans and orok-orok in Screenhouse. This research was conducted in Pest Laboratory and Screenhouse of the Agriculture Faculty, University of Sumatera Utara (±25 m asl) from March until August 2015. This research was using non-factorial Randomized Block Design with 3 treatments, which are soybeans, greenbeans and orok-orok with 9 replications. The result of this research showed that the pest R.linearis higher attacks on soybeans than greanbeans and orok-orok. The highest result in imago population of R. linearis was showed on soybeans (7.00), then on greenbeans (3.78), and orok-orok (1.22). The highest result in attacked pod percentage of R. linearis was showed on soybeans (81.88%), greenbeans (57.24%), and orok-orok (20.76%).